The treatment of penile carcinoma in situ (CIS) within a UK supra‐regional network. (15th December 2014) - Lucky, Marc; Murthy, Kusuma V.R.; Rogers, Beverley; Jones, Stephen; Lau, Maurice W.; Sangar, Vijay K.; Parr, Nigel J.
Abstract : Objectives: To review outcomes of the treatment of carcinoma in situ (CIS) of the penis at a large supra‐regional penile cancer network, where centralisation has permitted greater experience with treatment outcomes, and suggest treatment strategies. Patients and Methods: The network penile cancer database, which details presentation, treatment and complications was analysed from 2003 to 2010, identifying patients with CIS, with a minimum follow‐up of 2 years, looking at treatments administered and outcomes. Results: In all, 57 patients with mean (range) age of 61 (34–91) years were identified. In all, 18 were treated by circumcision only, 20 by circumcision and local excision (LE) and 19 by circumcision and 5‐flurouracil (5‐FU). The mean (range) follow‐up was 3.5 (2–8) years. Of those treated by circumcision none subsequently developed CIS on the glans. For those who underwent circumcision + LE, five of 20 (25%) developed recurrence requiring further treatment. Of those treated by circumcision + 5‐FU, 14/19 (73.7%) completely responded. Of the five incomplete responders, two had focal invasive malignancy at repeat biopsy. One incomplete responder underwent glansectomy and four grafting. No complete responders relapsed. Complications of 5‐FU included significant inflammatory response in seven (36.8%), with two requiring hospital admission and one neo‐phimosis (5.3%). Conclusion: This study suggests that patients undergoing circumcision for isolated CIS and complete responders to 5‐FU may require only short‐term follow‐up, as recurrence is unlikely, whereas longer follow up is required for all other patients. However, numbers in this study are small and larger studies are needed to support this. An incomplete response to 5‐FU dictates immediate re‐biopsy, as it carries a significant chance of previously undetected invasive disease.